Cutting-Edge Approaches to Emphysematous Pyelonephritis: Diagnosis, Management, and Future Directions - Arvind Ramachandran; Benjith Daniel F; Velmurugan Palaniyandi; Hariharasudhan Sekar; Sriram Krishnamoorthy (Newer Frontiers in Urology, Edition 1, 2025)
Introduction: Emphysematous Pyelonephritis (EPN) is a life-threatening infection characterized by gas formation within renal tissues, often associated with diabetes and immunocompromised states. Mortality rates were previously high, but advances in imaging, diagnosis, and treatment have improved outcomes. Aim: This study aims to review recent advancements in EPN management, from early diagnosis to current therapeutic approaches, while identifying areas for future research and innovation. Results: EPN is predominantly diagnosed in diabetic patients and those with urinary obstruction. Key pathogens include Escherichia coli and Klebsiella pneumoniae. Imaging, especially CT scan (Computed tomography), plays a critical role in classifying and managing EPN, with minimally invasive techniques such as percutaneous drainage emerging as effective interventions. Medical management, including strict glycaemic control and targeted antibiotics, has reduced the need for nephrectomy in lower-grade EPN cases. Conclusion: Advances in EPN management—diagnostic imaging, minimally invasive interventions, and improved medical therapy—have decreased mortality and morbidity. Future directions include predictive analytics for early diagnosis and novel antibiotics for resistant pathogens.